Global trends in income inequality and income dynamics: New insights from GRID - Fatih Guvenen; Luigi Pistaferri; Giovanni L. Violante (Quantitative Economics, 2022)
The Global Repository of Income Dynamics (GRID) is a new open-access, cross- country database that contains a wide range of micro statistics on income in- equality, dynamics, and mobility. It has four key characteristics: it is built on micro panel data drawn from administrative records; it fully exploits the longitudinal dimension of the underlying data sets; it offers granular descriptions of income inequality and income dynamics for finely defined subpopulations; and it is de- signed from the ground up with the goals of harmonization and cross-country comparability. This paper introduces the database and presents a set of global trends in income inequality and income dynamics across the 13 countries that are currently in GRID. Our results are based on the statistics created for GRID by the 13 country teams who also contributed to this special issue with individual articles.
Keywords: E24; J24; J31; 330; Administrative data; cross-country; database; granular; harmonized; inequality; longitudinal; mobility; volatility